2019
DOI: 10.1098/rspb.2018.2898
|View full text |Cite
|
Sign up to set email alerts
|

Local pesticide use intensity conditions landscape effects on biological pest control

Abstract: Complex landscapes including semi-natural habitats are expected to favour natural enemies thereby enhancing natural pest biocontrol in crops. However, when considering a large number of situations, the response of natural biocontrol to landscape properties is globally inconsistent, a possible explanation being that local agricultural practices counteract landscape effects. In this study, along a crossed gradient of pesticide use intensity and landscape simplification, we analysed the interactive effects of lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 49 publications
3
63
0
2
Order By: Relevance
“…A possible explanation is that the value of semi‐natural habitats for beneficial arthropods is dependent upon other local and landscape features. Local crop management such as within field rotation, fertilizer and pesticide applications, or the characteristics of field surroundings such as cropland composition, might strongly drive the level of pest control provided by natural enemies (Muneret et al., 2019; Ricci et al., 2019; Tscharntke et al., 2016), limiting the expected benefits of having abundant semi‐natural habitats in the landscape (Gagic et al., 2019; Rundlöf, Smith, & Birkhofer, 2016). Moreover, semi‐natural habitats may be more important for the temporal stabilization of resource availability in landscapes with simplified crop regimes (Schellhorn et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation is that the value of semi‐natural habitats for beneficial arthropods is dependent upon other local and landscape features. Local crop management such as within field rotation, fertilizer and pesticide applications, or the characteristics of field surroundings such as cropland composition, might strongly drive the level of pest control provided by natural enemies (Muneret et al., 2019; Ricci et al., 2019; Tscharntke et al., 2016), limiting the expected benefits of having abundant semi‐natural habitats in the landscape (Gagic et al., 2019; Rundlöf, Smith, & Birkhofer, 2016). Moreover, semi‐natural habitats may be more important for the temporal stabilization of resource availability in landscapes with simplified crop regimes (Schellhorn et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also revealed contrasting effects of AEI on weed seed or aphid suppression, depending on the local farming system and pesticide use intensity (i.e. positive effects under organic farming and low pesticide use intensity, negative ones under conventional farming and high pesticide use intensity) (Fischer et al, 2011;Winqvist et al, 2011;Ricci et al, 2019). All these results highlight the key role of organic farming to promote the spillover of predators from AEI towards cropped areas, most likely by increasing resource availabilitya major factor driving the movement of organisms between habitats (Dunning et al, 1992;Corbett and Plant, 1993;Blitzer et al, 2012;Tscharntke et al, 2016).…”
Section: Positive Effects Of Alley Cropping Agroforestry On Generalismentioning
confidence: 99%
“…Current evidence from field studies would suggest that present management strategies (increasing habitat complexity or implementing field margins) may fail to strongly promote resilience of natural pest control, at least in response to commonly used insecticides (Gagic et al, 2019;Ricci et al, 2019). In order for integrated pest management strategies to become a viable option in open arable systems, determining chemicals that maximally impact the pest species while having minimal impact on beneficial invertebrates is an important step.…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…beneficial predators). In many instances, broad‐spectrum insecticides not only diminish within‐field natural enemy populations, but nullify attempts to increase their populations (Gagic et al., 2019; Ricci et al., 2019). The obvious mechanism for the negative effects of insecticides on natural enemies is exposure leading to direct mortality (Guedes, Smagghe, Stark, & Desneux, 2016; Stark & Banks, 2003).…”
Section: Introductionmentioning
confidence: 99%